Additive mixture for mould material mixtures for producing moulds and cores for water-glass bonded foundries
Patent Information
- Application Number
- JP2021575512
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-17
- Filing Date
- 2020-06-15
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2040-06-15
Smart Images

Figure 0007652719000001 
Figure 0007652719000002 
Figure 0007652719000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to the use of an additive mixture (A) in combination with a solution or dispersion (B) comprising water glass to produce a mold material mixture for producing an article from the group consisting of foundry molds and foundry cores; a multi-component binder system comprising (A) such an additive mixture and (B) a solution or dispersion comprising water glass; a mold material mixture comprising a mold base material (C) and also the components (A) and (B) of such a multi-component binder system; a method for producing an article from the group consisting of foundry molds and foundry cores; an article from the group consisting of foundry molds and foundry cores; and the use of such an article for metal casting, preferably light metal casting, more particularly aluminum casting. [Background technology]
[0002] Foundry molds and foundry cores are produced from a mold material mixture. The basic components of the mold material mixture are a granular refractory mold matrix and a binder. In such foundry molds or foundry cores, the particles of the refractory mold matrix are bound to one another by the binder, thereby providing the necessary mechanical stability to the foundry mold or foundry core. Foundry molds contain cavities that are filled with a metal melt during casting to obtain the intended casting. In the production of foundry molds, a cavity is formed in the mold material mixture based on a model of the intended casting. Inserting a core into the mold forms all the internal contours of the casting. Both organic and inorganic binders for foundry molds and foundry cores are known. The advantage of inorganic binders is that harmful emissions to health and the environment are avoided.
[0003] US Pat. No. 4,162,238 discloses a mold material mixture having an inorganic binder comprising water glass and amorphous particulate silicon dioxide.
[0004] It is a known practice in the art to add additives to waterglass-based binders of the type described above in order to optimize the properties of foundry molds and foundry cores produced with the binder.
[0005] WO 2006 / 024540 A2 discloses mold material mixtures with a water-glass-based binder of the aforementioned type, which further contain organic additives having a melting point in the range of 40-180°C, preferably 50-175°C, and thus solid at room temperature. The organic additives are understood to be compounds whose molecular structure is primarily composed of carbon atoms, i.e., organic polymers, for example. The purpose of adding the organic additives is to achieve a further improvement in the surface quality of the casting.
[0006] WO 2008 / 046651 A1 discloses mold material mixtures with water glass-based binders of the aforementioned type, which mixtures also contain carbohydrates, the purpose of which is also to achieve a further improvement in the surface quality of the castings.
[0007] However, the use of organic additives defeats the purpose of avoiding effluents harmful to health and the environment.
[0008] Mold material mixtures having waterglass-based binders of the aforementioned type containing inorganic additives are also known.
[0009] WO 2008 / 046653 A1 discloses mold material mixtures with waterglass-based binders of the aforementioned type, which further contain a phosphorus-containing compound. The purpose of adding the phosphorus-containing compound is to increase the strength of the foundry mold and enable thinner sections to be realized without deformation during metal casting. The phosphorus-containing compound is preferably in the form of a phosphate or phosphorus oxide. The phosphate can be present as a phosphate salt of an alkali metal and / or alkaline earth metal, with alkali metal salts being particularly preferred, and in particular sodium salts. WO 2008 / 046653 A1 does not describe the effect of adding the phosphorus-containing compound on the surface quality of the casting and the adhesion of the mold matrix grains to the casting surface.
[0010] WO 2013 / 182186 A2 discloses mold material mixtures with a water glass-based binder, which further contain barium sulfate, the purpose of which is to reduce sand adhesion, sand burning, penetration and roughness on the surface of the casting.
[0011] DE 10 2012 113073 A1 discloses mould material mixtures with a water glass-based binder, which mixtures: - at least one aluminum oxide in the α phase, and / or - at least one mixed aluminum / silicon oxide, excluding mixed aluminum / silicon oxides with a phyllosilicate structure; The present invention further includes a particulate metal product comprising or consisting of:
[0012] The purpose of adding particulate metal oxides is to improve the surface of the casting.
[0013] German Patent No. 15 08 633 C discloses a mould composition for producing soluble moulds and cores for metal casting from a calcium phosphate-containing composition, characterized by a calcium phosphate content of at least 40 weight percent, a Ca content of 25-45 weight percent and a P content of 12-30 weight percent.
[0014] Further prior art is DE 103 23 079 A1 and DE 10 2016 205 729 A1. Summary of the Invention [Problem to be solved by the invention]
[0015] In the foundry industry, there is a constant need for inorganic additives for mold material mixtures with water glass-based binders of the above-mentioned type, which allow the production of water glass-bonded foundry molds and foundry cores, which result in castings that are distinguished by a smooth surface and low sand adhesion. [Means for solving the problem]
[0016] This object is achieved by the use of an additive mixture (A) in combination with a solution or dispersion (B) comprising water glass to produce a mold material mixture for producing articles from the group consisting of foundry molds and foundry cores; further aspects relate to a multi-component binder system for use in the present invention comprising (A) the additive mixture and (B) a solution or dispersion comprising water glass; a mold material mixture comprising a mold base material (C) and also the components (A) and (B) of the multi-component binder system of the present invention; a method for producing articles from the group consisting of foundry molds and foundry cores; articles from the group consisting of foundry molds and foundry cores; and the use of such articles for metal casting, preferably light metal casting, more particularly aluminum casting. DETAILED DESCRIPTION OF THE INVENTION
[0017] A first aspect of the present invention relates to the use of an additive mixture (A) for combining with a solution or dispersion (B) comprising water glass to produce a mold material mixture for producing articles from the group consisting of foundry molds and foundry cores, the additive mixture (A) comprising: (A-1) Particulate amorphous silicon dioxide, (A-2) Salt M(PO)OH (where M is an alkaline earth metal) and the additive mixture is a solid mixture or a suspension.
[0018] The additive mixture (A) for use in the present invention is intended to be combined with a solution or dispersion (B) containing water glass to produce a mold material mixture for producing articles from the group consisting of foundry molds and foundry cores. This means that in the production of such a mold material mixture, the mold base material is mixed with both the additive mixture (A) defined above and the solution or dispersion (B) containing water glass. Details of this are described below.
[0019] Surprisingly, it has been found that castings produced by casting foundry molds or cores from a water glass bonded mold material mixture containing the additive mixture for use in the present invention, which contains the above-mentioned specified salt (A-2), have smoother surfaces and less sand adhesion than castings produced under the same conditions by casting foundry molds or cores of the same shape from a water glass bonded mold material mixture having the same composition except that salt (A-2) is not present. This is particularly true in the case of water glass bonded foundry molds or foundry cores whose mold base material is silica sand.
[0020] Here, "sand adhesion" is understood to mean adhesion of particles of the mold matrix, regardless of the nature of the mold matrix (see below for details).
[0021] In salt (A-2), the alkaline earth metal M is preferably selected from the group consisting of calcium and barium. Salt (A-2) is preferably Ca5(PO4)3OH (pentacalcium triorthophosphate, pentacalcium tris(orthophosphate) hydroxide), also known as hydroxyapatite. It should be noted that salt (A-2) for use in the present invention is not the same as β-tricalcium phosphate Ca3(PO4)2. A commercially available product called "bone ash" also does not qualify as salt (A-2) for use in the present invention.
[0022] The median d 50Salts (A-2) having a particle size distribution of <20 μm, preferably <10 μm, more preferably <5 μm are preferred.
[0023] Particularly preferred is Ca5(PO4)3OH having a particle size distribution with a median <20 μm, preferably <10 μm, more preferably <5 μm, as measured by laser scattering (see examples for details).
[0024] This particle size distribution measurement by laser scattering is based on the relationship between the size of the particle on the one hand and the angle and intensity of the light scattered by this particle on the other hand. From the measured angle and intensity of the laser radiation scattered by the particles contained in the sample, information about the particle size can be obtained by algorithms based on Mie scattering theory.
[0025] For particles having a size of at least about 20 μm, a substantial contributor to light scattering is the diffraction of light incident on the particle surface. Thus, in this case, the particle size measurement method based on measuring the angle and intensity of the scattered light is often referred to as the "laser diffraction method."
[0026] However, for particles with a size less than about 20 μm, an important contributor to light scattering is not only the diffraction of light incident on the particle surface, but also the refraction of the light radiation passing through the particle. Therefore, in this case, the algorithm for calculating the particle size distribution must take into account the refractive index of the sample material.
[0027] The measurement of particle size distribution specified herein always takes into account the diffraction and refraction of laser radiation, and therefore the method is referred to herein as "particle size distribution measurement by laser scattering". However, the term "laser diffraction method" is often used in the prior art, even when both diffraction and refraction of laser radiation are taken into account.
[0028] The particulate amorphous silicon dioxide (A-1) is preferably - particulate synthetic amorphous silicon dioxide comprising at least carbon as a second component, the silicon dioxide fraction being 90% or more based on the total mass of the particulate synthetic amorphous silicon dioxide and the second component, the particulate synthetic amorphous silicon dioxide being preferably producible by reduction of quartz in an electric arc furnace; - particulate synthetic amorphous silicon dioxide containing an oxide of zirconium as a second component, preferably producible by thermal decomposition of ZrSiO4; - Particulate synthetic amorphous silicon dioxide, which can be produced by oxidation of silicon metal with an oxygen-containing gas; - granular synthetic amorphous silicon dioxide, which can be produced by rapid cooling of a silicon dioxide melt; - fumed silica, preferably producible by pyrolysis of silicon tetrachloride; and A mixture of them is selected from.
[0029] The term "particulate" refers to a solid powder (including dust) or a collection of granules that are preferably free-flowing and therefore sievable.
[0030] Synthetically produced particulate amorphous silicon dioxide in the sense of the present specification is - is the target product of a chemical reaction process designed to produce a technical synthesis of particulate amorphous silicon dioxide, or - means amorphous silicon dioxide that is a by-product of a chemical reaction process that is carried out in the course of a technical synthesis of a target product that is not particulate amorphous silicon dioxide.
[0031] An example of a reaction process in which particulate amorphous silicon dioxide is the target product is the flame hydrolysis of silicon tetrachloride. The particulate amorphous SiO2 ("silicon dioxide") produced by this method is also called "pyrogenic SiO2" ("pyrogenic silicon dioxide") or "fumed silica" (CAS RN 112945-52-5).
[0032] An example of a reaction process in which particulate amorphous silicon dioxide is formed as a by-product is the reduction of quartz using coke in an arc furnace, for example, to produce silicon or ferrosilicon as the target product. The particulate amorphous SiO2 ("silicon dioxide") formed in this manner is also called silica dust, silicon dioxide dust, or SiO2 fume condensate, or "silica fume," or microsilica (CAS RN 69012-64-2).
[0033] Another reaction process by which particulate amorphous silicon dioxide can be synthetically produced is the thermal decomposition of ZrSiO4 to ZrO2 and SiO2.
[0034] Particulate amorphous silicon dioxide can be obtained by oxidation of silicon metal with an oxygen-containing gas (for details, see DE 10 2012 020 510 A1) and also by quenching the silicon dioxide melt.
[0035] As used herein, both amorphous silicon dioxide formed by the flame hydrolysis of silicon tetrachloride and amorphous silicon dioxide obtained as a by-product of the reduction of quartz using coke in, for example, an arc furnace, and amorphous silicon dioxide formed by the thermal decomposition of ZrSiO4 are often referred to as "pyrogenic SiO2" ("pyrogenic silicon dioxide") or fumed silica.
[0036] As a concomitant of its production, particulate amorphous silicon dioxide of the type produced by the reduction of quartz with carbon (e.g., coke) in an arc furnace (in the production of ferrosilicon and silicon) contains carbon as a second component, the silicon dioxide fraction being 90% or more based on the total mass of the particulate synthetic amorphous silicon dioxide and the second component.
[0037] As a concomitant of its production, particulate amorphous silicon dioxide of the type produced by the thermal decomposition of ZrSiO4 contains an oxide of zirconium, particularly zirconium dioxide, as a second constituent.
[0038] In the case of particulate synthetic amorphous silicon dioxide, which can be produced by the oxidation of silicon metal with an oxygen-containing gas, and in the case of particulate synthetic amorphous silicon dioxide, which can be produced by rapid cooling of a silicon dioxide melt, the SiO2 is very pure, with very little unavoidable impurities (i.e., incidental to the production process).
[0039] Particularly preferred particulate amorphous silicon dioxide for use in connection with the present invention includes particulate amorphous silicon dioxide of the type identified by CAS RN 69012-64-2 or CAS RN 112945-52-5. These types are available as described above. Here, "CAS RN" stands for CAS registration number and CAS Registry Number; CAS = Chemical Abstracts Service.
[0040] Likewise particularly preferred are SiO2 produced by pyrolysis of ZrSiO4 to ZrO2, pyrolysis from ZrSiO4, and SiO2 obtained by flame hydrolysis of silicon tetrachloride.
[0041] The median diameter (d) of the nanoparticles ranges from 0.7 to 1.5 μm as measured by laser scattering (see Examples for details). 50 ) particle size distribution is preferred.
[0042] - the salt (A-2) is Ca5(PO4)3OH, and Particular preference is given to additive mixtures for use in the present invention in which the particulate amorphous silicon dioxide (A-1) is selected from the aforementioned options, more particularly from the aforementioned preferred options.
[0043] In one of the additive mixtures for use in the present invention, the ratio of the mass of particulate amorphous silicon dioxide (A-1) to the mass of salt (A-2) is preferably in the range of from 1:3 to 40:1, more preferably from 2:1 to 20:1, very preferably from 2:1 to 10:1, and ideally from 4:1 to 7:1.
[0044] In particularly preferred additive mixtures for use in the present invention, the ratio of the mass of particulate amorphous silicon dioxide (A-1) to the mass of Ca5(PO4)3OH is preferably in the range of from 1:3 to 40:1, more preferably from 2:1 to 20:1, very preferably from 2:1 to 10:1, and ideally from 4:1 to 7:1.
[0045] In a particular case, the additive mixture for use in the present invention consists of components (A-1) and (A-2), which means that it does not contain any further components. This type of additive mixture takes the form of a powder mixture.
[0046] Alternatively, the additive mixture for use in the present invention may comprise the above-defined components (A-1) and (A-2) together with additional components, and depending on the nature of these additional components, the additive mixture may take the form of a powder mixture or a suspension.
[0047] Examples of these further components are: - a liquid suspending medium, preferably water; surface-active substances, in particular surfactants, defoamers and wetting agents; - particulate inorganic materials (see below for more details); - alkali metal hydroxides; - organosilicon compounds, such as silanes, silicones and siloxanes; - wax; - Paraffin; - Metal soaps; carbohydrates, preferably selected from the group consisting of oligosaccharides, polysaccharides and mixtures thereof, more preferably selected from the group consisting of cellulose, cellulose esters, cellulose ethers, starch and dextrins; is.
[0048] The addition of such substances to mold material mixtures having water glass as binder is well known to those skilled in the art; in this regard, reference is also made to the prior art cited above.
[0049] The aforementioned particulate inorganic materials are also additives known to those skilled in the art to be added to mold material mixtures with water glass as a binder; in this regard, reference is also made to the prior art cited above. Preferred particulate inorganic materials are: - Aluminum oxide, preferably alpha phase; bauxite; mixed aluminum / silicon oxide; - oxides of zirconium, preferably zirconium(IV) oxide; - Zinc oxide; - barium sulfate; - a phosphorus-containing compound which is not a salt (A-2), preferably selected from the group of alkali metal phosphates; - phyllosilicates; - graphite, carbon black; - Glass beads; hollow ceramic beads; - magnesium oxide; boron oxide compounds, preferably selected from the group consisting of borates, boric acid, boric anhydride, borosilicates, borophosphates and borophosphosilicates; The material is selected from the group consisting of:
[0050] A further aspect of the present invention is (A) the aforementioned additive mixture; (B) Solution or dispersion containing water glass as spatially separated components.
[0051] "Water glass" is understood to include alkali metal silicates that can be obtained, for example, by co-melting silica sand with sodium carbonate or potassium carbonate at 1400-1500° C. or by hydrothermal methods. These alkali metal silicates are typically water-soluble.
[0052] The water glass for use in the present invention preferably contains one or more alkali metal cations from the group consisting of lithium, sodium and potassium, more preferably one or both alkali metal cations from the group consisting of sodium and potassium.
[0053] The SiO2 / M2O molar ratio of the water glass is preferably in the range of 1.6 to 4.0, and M2O means the total amount of oxides of alkali metals M.
[0054] In the present invention, water glass having a composition of M2OxSiO2, with a SiO2 / M2O molar ratio of the water glass ranging from 1.6 to 4.0, is preferred, where M2O means the total amount of oxides of alkali metals M selected from the group consisting of sodium and potassium.
[0055] Component (B) preferably has an alkali metal silicate content in the range of 20% to 60%, preferably in the range of 25% to 55%, based on the total mass of component (B).
[0056] In the multi-component binder system of the present invention, components (A) and (B) are separated from one another, i.e., they are present in separate containers. It is intended that the reaction between the water glass of component (B) and the particulate amorphous silicon dioxide of component (A) will only begin when the two components (A) and (B) are combined with a mold matrix and, optionally, further constituents to form an article from the group consisting of foundry molds and foundry cores.
[0057] In certain cases, component (B) of the multi-component binder system of the present invention consists of water and water glass dissolved and / or dispersed therein, which means that this component does not contain further constituents.
[0058] Alternatively, component (B) of the multi-component binder system of the present invention comprises not only water and waterglass dissolved and / or dispersed therein, but also further constituents.
[0059] Examples of these further components are: surface-active substances, in particular surfactants, defoamers and wetting agents; - alkali metal phosphates; boron oxide compounds, preferably selected from the group consisting of borates, boric acid and boric anhydride; is.
[0060] The addition of such materials to waterglass-based binders is well known to those skilled in the art.
[0061] Component (B) of the multi-component binder system of the present invention preferably comprises not only water and waterglass dissolved and / or dispersed therein, but also one or more surface-active substances, preferably from the group of surfactants, defoamers and wetting agents.
[0062] More preferably, component (B) of the multi-component binder system of the present invention comprises not only water and waterglass dissolved and / or dispersed therein, but also one or more surfactants.
[0063] When component (B) of the binder of the present invention contains components from the group consisting of boron oxide compounds and alkali metal phosphates, they are present in solution in the waterglass solution or dispersion. Such selected boron oxide compounds and alkali metal phosphates preferably have a solubility of 1 g / l of solvent. In this case, the solvent is the liquid phase of the solution or dispersion forming component (B), and in each case does not contain components from the group consisting of boron oxide compounds and alkali metal phosphates that are dissolved therein.
[0064] Component (A) of the binder of the present invention is preferably selected from the preferred additive mixtures described above.
[0065] A further aspect of the present invention relates to a mold material mixture containing (C) a mold base material and also containing components (A) and (B) of the multi-component binder system of the present invention described above, wherein the mold material mixture contains salt (A-2) at a concentration of 0.01% to 5% based on the total mass of the mold base material.
[0066] Surprisingly, it has been found that castings produced by casting from foundry molds or cores formed using the mold material mixture of the present invention have smoother surfaces and less sand adhesion than castings produced under the same conditions by casting from foundry molds or cores of the same shape formed from the same mold material mixture except for the absence of salt (A-2). This is particularly true in the case of water-glass bonded foundry molds or foundry cores whose mold base material is silica sand.
[0067] With respect to the preferred components (A) and (B) of the multi-component binder system of the present invention, the above comments are valid.
[0068] The term "mold matrix" includes not only individual materials suitable as mold matrices, but also mixtures of different materials suitable as mold matrices.
[0069] Suitable mold matrices are any mold matrices commonly used in the production of foundry moulds and foundry cores, examples being quartz sand and special sands. The term "special sand" includes natural mineral sands and inorganic mineral sands produced in granular form and / or obtained by sintering and melting or other physicochemical processes that are converted into granular form by crushing, grinding and classification operations, and that are used as mold matrices with typical foundry binders for the production of feeders, cores and moulds. Special sands include: aluminum silicates in the form of natural minerals or mineral mixtures, such as J sand and Kerphalite KF; - aluminum silicates in the form of technical sintered ceramics, such as chamotte and Cerabeads, - Natural heavy minerals, such as R sand, chromite sand and zircon sand, - technical oxide ceramics, such as M sand and bauxite sand, and - Technical non-oxide ceramics, e.g. silicon carbide Examples include:
[0070] The mold matrix is preferably a refractory mold matrix. "Refractory" in this specification, consistent with the common understanding of those skilled in the art, refers to compositions, materials, and minerals that can withstand, at least for a short time, the temperature loads during casting and / or solidification of the metal melt. Suitable mold matrixes are natural and synthetic mold matrixes, examples of which are silica sand, zircon or chromite sand, olivine, vermiculite, bauxite, or chamotte.
[0071] The mold base material (C) preferably contains silica sand, and is particularly preferably silica sand.
[0072] The mold matrix preferably accounts for more than 80% by weight, more preferably more than 90% by weight, and most preferably more than 95% by weight of the total mass of the mold material mixture of the present invention (as defined above). The mold matrix is preferably in a free-flowing state. Therefore, the mold matrix for use in the present invention is preferably in granular or particulate form.
[0073] In the mold material mixture of the present invention, the concentration of particulate amorphous silicon dioxide (A-1) is preferably 0.05% to 3.0%, more preferably 0.1% to 2.0%, and most preferably 0.3% to 1.5%, based on the total mass of the mold base material.
[0074] In the mold material mixture of the present invention, the total concentration of salt (A-2) is 0.01% to 5%, preferably 0.02% to 2%, more preferably 0.05% to 1%. The mold material mixture preferably contains salt (A-2) Ca5(PO4)3OH in a concentration of 0.01% to 5%, more preferably 0.02% to 2%, and most preferably 0.05% to 1%, based on the total mass of the mold base material.
[0075] In the mold material mixture of the present invention, the total concentration of water glass is preferably 0.2% to 3%, more preferably 0.3% to 2%, based on the total mass of the mold base material.
[0076] Particularly preferably, the inventive mold material mixture comprises, in each case based on the total weight of the mold base material: particulate amorphous silicon dioxide (A-1) in a concentration of 0.05% to 3.0%, preferably 0.1% to 2.0%, more preferably 0.3% to 1.5%, salt (A-2) at a concentration of 0.01% to 5%, preferably 0.02% to 2%, more preferably 0.05% to 1%, - Water glass in a concentration of 0.2% to 3%, preferably 0.3 to 2% Includes.
[0077] Particularly preferably, the inventive mold material mixture comprises, in each case based on the total weight of the mold base material: particulate amorphous silicon dioxide (A-1) in a concentration of 0.05% to 3.0%, preferably 0.1% to 2.0%, more preferably 0.3% to 1.5%, Ca5(PO4)3OH at a concentration between 0.01% and 5%, preferably between 0.02% and 2%, more preferably between 0.05% and 1%, - Water glass in a concentration of 0.2% to 3%, preferably 0.3 to 2% Includes.
[0078] The mold material mixture of the present invention preferably contains calcium phosphates (i.e., Ca5(PO4)3OH and other calcium phosphates, such as β-tricalcium phosphate Ca3(PO4)2) in a total amount of not more than 10%, preferably not more than 8%, more preferably not more than 6%, in each case based on the total mass of the mold base material.
[0079] The mold material mixture of the present invention preferably contains alkaline earth metal phosphates (i.e., the salt (A-2) defined above and alkaline earth metal phosphates other than salt (A-2)) in a total amount of 10% by weight or less, preferably 8% by weight or less, more preferably 6% by weight or less, in each case based on the total mass of the mold base material.
[0080] The template material mixture of the present invention preferably does not contain an alkaline earth metal phosphate that is not the above-specified salt (A-2).
[0081] The mold material mixture of the present invention is preferably in a free-flowing form so that it can be easily introduced into a mold and compressed therein when molded. Compression of the mold material mixture in the mold serves to increase the strength of the foundry mold or foundry core produced from the mold material mixture.
[0082] The mold material mixture of the present invention comprises: - providing a mold base material (C); - mixing the components (A) and (B) of the multi-component binder system into the mold matrix (C). The composition can be produced by a method comprising:
[0083] In this case, the spatially separated components (A) and (B) of the multi-component binder system are mixed simultaneously or successively into the mold base material (C). In a specific case, it is preferred to first mix the additive mixture (A) into the mold base material (C) to form a premix containing the mold base material (C) and the additive mixture (A), and then mix the water glass-containing solution or dispersion (B) into the resulting premix to obtain the mold material mixture. In another case, it is preferred to first mix the water glass-containing solution or dispersion (B) into the mold base material (C) to form a premix containing the mold base material (C) and the water glass, and then mix the additive mixture (A) into the resulting premix.
[0084] A further embodiment includes a method for producing an article from the group consisting of foundry molds and foundry cores, the article being formed by combining a mold base material (C) with components (A) and (B) of the multi-component binder system of the present invention as defined above, and heat curing the binder.
[0085] Here, the combination of the mold base material (C) with the components (A) and (B) of the multi-component binder system of the present invention as defined above can be completed before the binder system is heat-cured; in other words, first a molded mold material mixture is formed and the binder system is heat-cured in the molded mold material mixture.
[0086] In another variant, combining the mold matrix (C) with the components (A) and (B) of the inventive multi-component binder system as defined above and heat-curing the binder system is carried out in several successive cycles, in which in each cycle the mold matrix (C) is combined with the components (A) and (B) of the inventive multi-component binder system as defined above and the binder system is heat-cured, in which articles from the group consisting of foundry molds and foundry cores are built up layer by layer.
[0087] The term "thermal curing" is understood to mean that the binder system during curing is exposed to temperatures above 100°C, preferably to temperatures between 100°C and 300°C, more preferably to temperatures between 120°C and 250°C.
[0088] The thermal hardening of the binder system occurs due to the chemical reaction of the components of the binder system with one another, resulting in the formation of a foundry mold or foundry core. The thermal hardening of the binder system is essentially caused by the condensation of the water glass, i.e., the bonding of the silicate units of the water glass with one another (the reaction mechanism is comprehensively described in the technical literature). Therefore, water is removed from the binder system as a result of the heat treatment.
[0089] In one preferred variant, the method of the invention comprises: - producing the inventive mould material mixture as defined above, - shaping the mold material mixture, preferably in a mold; - heat-curing the binder system in the molded mold material mixture; Includes.
[0090] The mold material mixture is preferably introduced into the mold by compressed air.
[0091] Heating of the shaped mold material mixture for thermal curing of the binder system can be carried out, for example, in a mold having a temperature above 100° C., preferably a temperature between 100° C. and 300° C., more preferably a temperature between 120° C. and 250° C. The thermal curing of the binder system in the shaped mold material mixture is preferably carried out completely or at least partially in a conventional mold for the industrial production of molded articles.
[0092] Here, the thermal hardening of the binder system in the molded mold material mixture can be carried out in suitable facilities and / or using suitable equipment (lines, pumps, etc.), and is assisted by controlled gas treatment of the molded mold material mixture with temperature-regulated air. The air used for this purpose is preferably regulated to a temperature between 100°C and 250°C, more preferably between 110°C and 180°C. Although air contains carbon dioxide, in the sense of the present invention, this does not correspond to the CO2 method known in the prior art for hardening water glass, which is based in particular on deliberate gas treatment of the molded mold material mixture with CO2-rich gas in suitable facilities and / or using suitable equipment (lines, pumps, etc.). Therefore, gas treatment of the molded mold material mixture with a gas containing CO2 at a concentration higher than that in air is preferably not carried out or combined with the thermal hardening envisaged in the present invention.
[0093] The heat-setting time, and therefore the heating time and the time of deliberate gassing of the molded mold material mixture with temperature-regulated air, can vary depending on the requirements of the situation under consideration and can be influenced, for example, by the size and geometric shape of the molded mold material mixture. The flow rate and / or volumetric flow rate of the temperature-regulated air during the deliberate gassing of the molded mold material mixture is preferably set so that the hardening achieved in the molded mold material mixture is sufficient for further functions and / or applications within a very short time acceptable for industrial use (see below for details). In the context of the present invention, times of less than 5 minutes are preferred, more preferably less than 2 minutes. However, for very large molds or cores, longer times may be necessary depending on the requirements of the situation under consideration.
[0094] The molded mold material mixture can be allowed to harden primarily within the mold itself.
[0095] However, the method of the present invention does not assume that complete hardening of the binder system occurs during the heat-hardening step. Therefore, as mentioned above, "heat-hardening" in the sense of the method of the present invention also includes incomplete hardening of the binder. This is true of the understanding of the term "hardening" by those skilled in the art, since, for reasons of reaction kinetics, it is unlikely that the binder system in the entire volume of the molded mold material mixture will react during the relatively short heat-hardening step. Thus, for example, the phenomenon of post-hardening of (e.g., heat-hardened) binder systems in foundry molds or foundry cores is known to those skilled in the art.
[0096] Therefore, according to the present invention, it is also possible to initially harden the binder system in the mold only in the peripheral region of the molded mold material mixture in order to achieve sufficient strength (green strength) for the molded mold material mixture to be removed from the mold. The molded mold material mixture can then be further hardened by further removal of water (e.g., by evaporation of water in an oven or under vacuum or in a microwave oven).
[0097] Heat curing can be induced or assisted by exposing the shaped mold material mixture to microwave or electromagnetic radiation, especially infrared radiation.
[0098] Similarly, thermal hardening can be induced or assisted by passing an electric current through the molded mold material mixture, preferably a uniform, more preferably evenly distributed electric current, and / or by applying a preferably uniform, more preferably evenly distributed electromagnetic field through and / or onto the molded mold material mixture, respectively. In this way, the mold material mixture is heated, preferably uniformly, and ultimately hardens in a particularly uniform manner that results in high quality. Further details are disclosed in DE 10 2017 217098 B3 and the documents cited therein.
[0099] The inventive articles from the group consisting of the aforementioned foundry molds and foundry cores can also be obtained through layer-by-layer deposition by 3D printing, corresponding methods being known, for example, from DE 10 2014 118 577 A1 and DE 10 2011 105 688 A1.
[0100] The method of the invention, which is a progressive development of the method known from DE 10 2014 118 577 A1 for the layer-by-layer deposition of elements, comprises a) providing a premix comprising a mold base material (C) and an additive mixture (A); b) applying a thin layer of premix with a layer thickness of 0.05 mm to 3 mm, preferably 0.1 mm to 2 mm, more preferably 0.1 mm to 1 mm, c) printing (B) a solution containing water glass in selected areas of the thin layer (corresponding to the shape of the article being manufactured); d) repeating steps b) and c) to deposit, layer by layer, articles from the group consisting of foundry molds and foundry cores. Includes.
[0101] The printed areas are in each case hardened after depositing 1 to 10 printed layers, preferably by exposure to microwaves or electromagnetic radiation.
[0102] The method of the present invention, which is a progressive development of the method known from DE 10 2011 105 688 A1 for layer-by-layer deposition of models, comprises applying a premix comprising a mold base material (C), the aforementioned additive mixture (A) and water glass (in the form of a spray-dried alkali metal silicate solution) layer by layer and selectively thermally curing (corresponding to the shape of the article being produced), these steps being repeated until the desired article is obtained; this selective curing comprises activating the curing with a water-containing solution and drying, wherein the water-containing solution for selective curing is preferably applied using an inkjet printhead, preferably using piezo technology, and / or the curing is accelerated by thermal convection and / or thermal radiation.
[0103] A further aspect relates to an article from the group consisting of foundry molds and foundry cores, which comprises a mold base (C) that can be produced by the aforementioned method of the present invention and / or is bound by the hardened product of the aforementioned binder of the present invention and salt (A-2) at a concentration of 0.01% to 5% based on the total mass of the mold base.
[0104] The article preferably comprises Ca5(PO4)3OH at a concentration of 0.01% to 5% based on the total mass of the mold matrix.
[0105] Surprisingly, it has been found that castings produced by casting the foundry molds and / or cores of the present invention have smoother surfaces and less sand adhesion than castings produced under the same conditions by casting foundry molds or cores of the same shape and composition, except that the salt (A-2) is absent. This is particularly true in the case of water-glass bonded foundry molds or foundry cores in which the mold matrix is silica sand.
[0106] Castings produced using the foundry mold and / or foundry core of the invention have high casting surface quality; in particular, roughness and sand adhesion occur only to a very low extent. This is particularly true for foundry molds and / or foundry cores of the invention in which the mold matrix is silica sand.
[0107] A further aspect of the present invention relates to the use of an article according to the invention from the group consisting of foundry molds and foundry cores for metal casting, preferably light metal casting, more particularly aluminium casting.
[0108] A further aspect of the present invention relates to the use of the additive mixture (A) as a component of the aforementioned inventive multicomponent binder system or the aforementioned inventive mold material mixture for producing articles from the group consisting of foundry molds and foundry cores.
[0109] Surprisingly, it has been found that castings produced by casting foundry molds and / or cores from a water glass bonded mold material mixture containing the additive mixture for use in the present invention, which contains the above-mentioned specified salt (A-2), have smoother surfaces and less sand adhesion than castings produced under the same conditions by casting foundry molds and / or cores of the same shape from a water glass bonded mold material mixture having the same composition except that salt (A-2) is not present. This is particularly true in the case of water glass bonded foundry molds and / or foundry cores whose mold base material is silica sand.
[0110] A further aspect of the present invention is to provide an additive mixture, i.e., component (A) of the multi-component binder system of the present invention, comprising: (A-2) Salt M(PO)OH (where M is an alkali metal) In this case, it is preferable to use the salt Ca5(PO4)3OH.
[0111] The present invention will now be further described with reference to non-limiting examples and comparative examples. [Example]
[0112] 1. Manufacturing of test specimens To prepare the mold material mixture: (A-1) Particulate amorphous silicon dioxide (product "RW-Fueller Q1 Plus" RW Silicium GmbH Rottwerk Pocking, obtained by thermal decomposition of ZrSiO4, (A-2) Ca5(PO4)3OH (present invention; supplier: Budenheim, see Table 1 below), or Non-Inventive Additives (See Table 1 below for details) The additive mixture (A) containing the above was manually stirred into the mold base material (C) (H31 sand) that had been introduced previously, to obtain a premix containing the mold base material (C) and the additive mixture (A).
[0113] Next, (B) an aqueous solution, 36.2% by weight of sodium potassium water glass having a molar ratio of 2.1 and a Na2O / K2O ratio (molar) of about 7.7; 2.0% by weight of a surface-active substance, e.g., a wetting agent, e.g., sodium 2-ethylhexyl sulfate EHS 40 (supplier: Hoesch); (in each case based on the total mass of component (B)) An aqueous solution containing was added to the premix and the components of the mold material mixture were mixed in a Bull mixer (Morek Multiserver) at 220 rpm for 120 seconds.
[0114] To prepare a non-invention reference mixture: (A-1) Particulate amorphous silicon dioxide (see above for product details) was manually stirred into the mold base material (C) (H31 sand) previously introduced to obtain a premix containing the mold base material (C) and particulate amorphous silicon dioxide (A-1).
[0115] Next, (B) Aqueous solution containing water glass (concentration and composition as described above) was added to the premix and the ingredients of the mold material mixture were mixed in a Bull mixer (Morek Multiserver) at 220 rpm for 120 seconds.
[0116] The compositions of all mold material mixtures prepared are reported in Table 1. In Table 1, "pbw" stands for "parts by weight."
[0117] The mold material mixtures obtained in this way were each introduced into a mold with a core box temperature of 180°C using compressed air (4 bar = 400 kPa). The shooting time was 3 seconds, followed by a curing time of 30 seconds (delay time 3 seconds). During the entire curing time, the cores were further gassed with hot air (180°C, 2 bar = 200 kPa). Each shot produced three bending bars with dimensions of 22.4 mm x 22.4 mm x 186 mm.
[0118] [Table 1]
[0119] The various types of Ca5(PO4)3OH (A-2) of the present invention (each distinguished by a different product number) differ in their particle size. The median particle size distribution (d) of the additives in Mixes B and D to F measured by laser scattering is 50 ) are reported in Table 1a.
[0120] [Table 2]
[0121] 2. Test Method 2.1 Measurement of particle size distribution Approximately one teaspoon each of granular amorphous silicon dioxide (A-1) "RW-Fueller Q1 Plus" and phosphate additive (see Table 1a) was mixed with approximately 100 ml of fully demineralized (FD) water, and the resulting batch was stirred for 30 seconds using a magnetic stirrer (IKAMAG RET) at a stirring speed of 500 rpm. Subsequently, an ultrasonic probe (Hielscher; model UP200HT) pre-set to 100% amplitude and equipped with an S26d7 sonotrode (Hielscher) was immersed in the sample and used to sonicate the sample. Here, sonication was continuous (not pulsed). Stirring was continued during sonication of the phosphate sample.
[0122] The optimal sonication time, which depends on the particle type, was confirmed by performing a measurement series using multiple samples of each type and varying the sonication time in each series. The sonication time, starting at 10 seconds, was increased for each additional sample. Immediately after sonication, the particle size distribution was determined in each case by laser scattering (LA-960) as described below. As the sonication time increased, the measured median particle size distribution initially decreased, eventually increasing again with further increases in sonication time. The sonication time that yielded the lowest median particle size distribution was the optimal sonication time. For the RW-Fueller Q1 Plus, the optimal sonication time was 240 seconds. For the individual phosphate additives, the respective optimal sonication times are reported in Table 1a.
[0123] Particle size distribution was measured using a Horiba LA-960 instrument (hereafter referred to as LA-960). For the measurements, the circulation speed was set to 6, the stirring speed to 8, the sample data recording to 30,000, the convergence factor to 15, the distribution type to volume, the refractive index (R) of the particulate amorphous silicon dioxide was set to 1.50-0.01i (FD water as the dispersing medium was 1.33), and the refractive index (B) was set to 1.50-0.1i (FD water as the dispersing medium was 1.33). The refractive index (R) and (B) (both identical) settings for the phosphate additive are reported in Table 1a. Laser scattering measurements were performed at room temperature (20-25°C).
[0124] The measurement chamber of the LA-960 was filled three-quarters full with fully demineralized water (FD water) (maximum fill level). The agitator was then started at the specified settings, the circulation was switched on, and the water was degassed. A blank measurement was then performed using the specified parameters.
[0125] Immediately after sonication, a 0.5-3.0 ml volume was withdrawn from the center of the sample prepared as described above using a disposable pipette. The entire contents of the pipette were then introduced into the measurement chamber so that the red laser transmittance was 80%-90% and the blue laser transmittance was 70%-90%. Measurements were then initiated. Measurements were automatically evaluated based on the specified parameters.
[0126] In the case of particulate amorphous silicon dioxide (A-1) "RW-Fueller Q1 Plus", a median diameter (d 50 ) particle size distribution was obtained. In the case of the phosphate additive, the median (d 50 ) are reported in Table 1a.
[0127] 2.2 Measurement of bending strength To determine flexural strength, the prepared test bars were inserted into a Georg-Fischer strength testing apparatus equipped with a three-point bending fixture (manufactured by Multiserw) and the force required to break the test bar was measured. Flexural strength was measured 15 seconds (hot strength) or 1 hour (cold strength) after removal from the forming tool. The resulting measurements are reported below as the median of three measurements, rounded to the nearest integer divisible by 10.
[0128] 2.3 Measurement of core weight Core weights were measured using a standard commercial laboratory balance and are reported as the median of nine measurements.
[0129] 2.4 Casting quality evaluation Casting experiments were conducted with aluminum alloys to evaluate the effect of the composition of the mold material mixture on the casting surface and the amount of sand adhesion on the casting. For these experiments, one core per mold material mixture (mold material mixtures A, B, C, D, E, and F; see Table 1 above)—thus a total of six cores—was installed in an external sand mold so that three of the four long sides of the core were in contact with the melt during the casting process. Three sand molds were made in this manner, and the cores of mold material mixtures A, B, C, D, E, and F were placed in different positions in each mold. Aluminum alloy (EN AC-43000) was cast at a casting temperature of approximately 745°C. After the melt in the sand mold was cooled, the casting was removed from the sand mold, the core was removed by hammering, and the surface of the casting that had come into contact with the core was blasted with air from a compressed air gun.
[0130] To compare the relative quality of the castings, the sand adhesion on the casting surface in contact with the core was rated on a scale of 1 to 6 (1 being the best quality, i.e., very little sand adhesion, and 6 being the worst quality, i.e., a lot of sand adhesion), and the total for all three molds was calculated. The evaluations were carried out independently by two people (1) and (2), and then the totals were averaged. Furthermore, the amount of sand adhesion was evaluated, especially in comparison with the castings made with the cores from Mixture A (without additives).
[0131] 3. Experimental Results 3.1 Core weight and bending strength The observed core weights and flexural strengths can be taken from Table 2.
[0132] Serving as a reference is Mix A (without additives). The results show that the addition of both the additive for use in accordance with the invention (A-2) and the non-inventive additives β-tricalcium phosphate (Mix E) and Alodur ZK SF (a by-product of zircon corundum production, in dust form, manufactured by Treibacher Schleifmittel, Mix F) results in a slight reduction in core weight. The hot strength, which is important for practical use, is not affected (±10 N / cm2 The variation in the cold strength is within the limits of measurement accuracy. 2 Nevertheless, the cold strength achieved is immediately sufficient for use of cores in mass production.
[0133] [Table 3]
[0134] 3.2 Casting quality An evaluation of the casting surface and sand adhesion compared to a casting made with a core from Mixture A (without additives) can be taken from Table 3.
[0135] Serving as a reference are castings made with cores from mixture A (without additives). These cores had numerous sand deposits.
[0136] A clear reduction in sand adhesion was achieved using cores from the mold material mixture of the invention compared to cores from all non-inventive mixtures, especially those made from reference mixture A.
[0137] Surprisingly, in fact, with cores from the inventive mold material mixtures B, C and D, substantially better results are achieved than with cores made from the non-inventive mold material mixture F containing the additive Alodur ZK SF (a by-product of zircon corundum production, in dust form, from Treibacher Schleifmittel) according to DE 10 2012 113 073 A1, and the casting surface quality is improved in the case of grey cast iron.
[0138] When tested for comparison purposes with the additive β-tricalcium phosphate (mixture E), no significant improvement was realized compared to the reference mix A without the additive.
[0139] [Table 4]
Claims
1. (C) a mold base material; The following components (A) and (B): (A) an additive mixture comprising: (A-1) particulate amorphous silicon dioxide, (A-2) Salt Ca 5 (P.O. 4 ) 3 O.H. an additive mixture which is a solid mixture or a suspension, (B) Solution or dispersion containing water glass and a multi-component binder comprising 1. A mold material mixture comprising: Based on the total mass of the mold base material, said particulate amorphous silicon dioxide in a concentration ranging from 0.05% to 3.0%; the salt Ca 5 (PO 4 ) 3 OH in a concentration between 0.01% and 1%, and - said water glass at a concentration between 0.2% and 3% The mold material mixture comprising:
2. For producing the mold material mixture according to claim 1, The following components (A) and (B): (A) an additive mixture comprising: (A-1) particulate amorphous silicon dioxide, (A-2) Salt Ca5(PO4)3OH an additive mixture which is a solid mixture or a suspension, (B) Solution or dispersion containing water glass as spatially separated components from each other.
3. The particulate amorphous silicon dioxide (A-1) - particulate synthetic amorphous silicon dioxide comprising at least carbon as a second constituent, the fraction of silicon dioxide being greater than or equal to 90% based on the total mass of said particulate synthetic amorphous silicon dioxide and said second constituent; - microsilica (CAS RN 69012-64-2); - particulate synthetic amorphous silicon dioxide containing as a second component an oxide of zirconium; - fumed silica (CAS RN 112945-52-5); - Pyrogenic silicon dioxide and A mixture of them 3. Use of the multi-component binder according to claim 2, selected from the group consisting of
4. 4. Use of a multicomponent binder according to claim 2 or 3, wherein in the additive mixture (A) the ratio of the mass of particulate amorphous silicon dioxide (A-1) to the mass of salt (A-2) is in the range from 1:3 to 40:
1.
5. said waterglass in component (B) comprises cations of one or more alkali metals M from the group consisting of lithium, sodium and potassium, and / or Use of a multicomponent binder according to any one of claims 2 to 4, wherein component (B) has an alkali metal silicate content in the range of 20% to 60%, based on the total weight of component (B).
6. 5. A method for producing an article selected from the group consisting of foundry moulds and foundry cores, said article being formed by combining a mould base material (C) with the components (A) and (B) of the multi-component binder according to any one of claims 2 to 4 and heat curing said multi-component binder.
7. - Producing a mould material mixture according to claim 1, - shaping said mould material mixture; - heat curing the multi-component binder in the molded mould material mixture; The method of claim 6, comprising:
8. The method according to claim 6 or 7, wherein the heat curing is carried out at a temperature in the range of 100°C to 300°C.
9. The method of claim 6 , wherein the article is formed through layer-by-layer deposition.
10. An article selected from the group consisting of foundry molds and foundry cores, An article comprising a mold base material (C) bound by a hardened product of the multi-component binder according to any one of claims 2 to 5 and a salt (A-2) having a concentration of 0.01% to 1% based on the total mass of the mold base material.
11. Use of the article according to claim 10 for metal casting.
12. Use of the additive mixture (A) according to any one of claims 2 to 5 for producing articles selected from the group consisting of foundry moulds and foundry cores.
13. 10. The method of claim 2, further comprising the steps of: producing component (A) of the multicomponent binder according to claim 2, and reducing adhesion of particles of the mold base material to the casting; (A-2) Salt Ca 5 (P.O. 4 ) 3 O.H. Use of.
Citation Information
Patent Citations
High-thermal-conductivity composite modified sodium silicate sand for pump valve castings, and preparation method thereof
CN105414459A
Losing core for casting of self-hardening ceramic and manufacture thereof
JP1990258141A
Casting mold and its manufacturing method
JP2005224833A
Method of controlling elution of fluorine and inorganic porous material
JP2010115593A
Coated sand production method, coated sand obtained by the same, and cast production method
JP2014117740A